The production of postcards by J. Lacoste - Díaz Francés, Maite (Revista General de Información y Documentación, 2024)
In February 1900, Joseph Jean Marie Lacoste Borde acquired both the business and the prestigious collection of city views, monuments, customs, and works of art from the Casa Laurent. In so doing, José Lacoste became not just the successor of a great photographic archive, but the restorer of the old firm’s commercial production. He did this by focusing his efforts on a fashionable format: the postcard, both in its phototype and photographic versions. Through a bibliographic and documentary review, this study aims to provide a general overview of the production of postcards created, produced, and edited by José Lacoste between 1900 and 1914, shedding light on the evolution of such production. The study focuses on Lacoste's modus operandi, how it led to changes in the commercial enterprise, how these changes were reflected in the postcards, and to what extent the prestigious production of Casa Laurent influenced the choice of themes. Delving into these aspects allows us to establish new chronologies, discover new productions and editions, and learn about José Lacoste´s facets as a photographer, editor, and producer. In essence, highlighting how a small change in the commercial strategy, such as the introduction of a new format, could not only renew and consolidate Lacoste in the photographic market but restore the splendor and prolong the memory of Casa Laurent's work.
Keywords: José Lacoste; Casa Laurent; postcard; phototype; photography; artistic typology